1995
DOI: 10.1080/00380768.1995.10419563
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and silicon binding compounds in cell walls of rice shoots

Abstract: Calcium compounds in cell walls of rice shoots were investigated by molecular sieve chromatography and compared with silicon compounds. The phenolcarbohydrate complexes (PCC) obtained by eellulase action, and the lignincarbohydrate complexes (LCC) extracted by dimethylsulfoxide (DMSO) were loaded onto a Sephacryl S-400 column. Then calcium, silicon, phenolic acids, or lignin, and carbohydrate of both complexes were detected in the void volume. These results indicate that calcium and silicon may combine with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(41 citation statements)
references
References 9 publications
1
39
0
1
Order By: Relevance
“…In rice, silica accumulates mainly on cell walls, forming silicacuticle double layers and silica-cellulose double layers in the surface of leaves, stems and hulls . It was also suggested that silica is combined in some way with phenol-polysaccharide or lignin-polysaccharide compounds (Inanaga and Okasaka 1995). In fact, in vitro simulation experiments showed that silica deposition in aqueous borax solution is induced by the addition of soluble lignin from rice (Fang and Ma 2006).…”
mentioning
confidence: 99%
“…In rice, silica accumulates mainly on cell walls, forming silicacuticle double layers and silica-cellulose double layers in the surface of leaves, stems and hulls . It was also suggested that silica is combined in some way with phenol-polysaccharide or lignin-polysaccharide compounds (Inanaga and Okasaka 1995). In fact, in vitro simulation experiments showed that silica deposition in aqueous borax solution is induced by the addition of soluble lignin from rice (Fang and Ma 2006).…”
mentioning
confidence: 99%
“…1). Similar silicon-containing high molecular weight compounds were detected in the void volume by molecular sieve open-column chromatography of cellulase digests of rice cell walls 10 . It should be noted that the samples grown without silicic acid also gave the peak at void volume.…”
Section: Resultsmentioning
confidence: 84%
“…The suspensions were centrifuged and the insoluble residues washed with water. The solubilized material was dialyzed against deionized H 2 O with 10,000 mol wt cut dialysis membrane (Amicon Hollow fiber HIP [10][11][12][13][14][15][16][17][18][19][20]. The retentate was freeze-dried, and then loaded onto a column (1.6 × 90 cm) of Sephadex G-75, equilibrated with 50 mM ammonium formate buffer, pH 5.3, and eluted with the same buffer.…”
Section: Purification Of Silicon Containing Macromoleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sabe-se que o ácido monosilícico compete com o Ca pelos sítios de ligações na parede celular devido a sua facilidade em complexar-se com alcoóis polihídricos, ácidos orgânicos, lignina, carboidratos e até mesmo certos compostos fenólicos (Inanaga & Okasaka, 1995). Não houve diferença significativa (P ≥ 0,05) entre as duas cultivares para a concentração foliar de Si e a AACPMM; entretanto a concentração foliar de Ca foi significativamente superior para a cultivar BR-18 do que para a cultivar BRS-208.…”
unclassified